Ant exclusion and reproduction of Croton sarcopetalus (Euphorbiaceae) - Freitas, L. [UNESP]; Galetto, L. [UNESP]; Bernardello, G. [UNESP]; Paoli, Adelita Aparecida Sartori [UNESP] (My University, 2000)
A total of 20 insect species were observed on the extrafloral nectaries (EFNs) of Croton sarcopetalus. The most frequent ant species were Zacryptocerus sp., Crematogaster brevispinosa, C. scelerata, and Linepithema humile. Ants continuously patrolled the plants taking extrafloral nectar. Experimental data showed that there were no significant differences in either the degree of herbivory or in the reproductive output between control stems (with ants) and treated ones (without ants). We found no significant evidence of protection by ants mediated by EFNs in C. sarcopetalus. It is possible that the plant has other mechanisms than ant protection to prevent herbivore damage (e.g., hairs, latex, chemical defense). As this species occupies the southernmost distribution for the genus, the presence of EFNs in this species may be the remnant of a mutualistic interaction with the ants in tropical regions, where the abundance and diversity of ants and herbivores are comparatively higher. To draw accurate patterns in the genus Croton, further investigations in other species from tropical regions of South America are needed.
Keywords: Ant-plant interactions; Argentina; Chaco Serrano forests; Fruit set; Leaf predation; ant; antiherbivore defense; herbivory; nectar; Animalia; Chaco; Crematogaster brevispinosa; Crematogaster scelerata; Croton; Croton sarcopetalus; Euphorbia; Euphorbiaceae; Formicidae; Hexapoda; Hymenoptera; Insecta; Linepithema humile; Zacryptocerus